Social Pedagogy as a Scientific Discipline a Branch of Academic Studies and a Field of Professional Practice - Juha Hämäläinen (Universidade Nove de Julho, 2019)
This article is based on productions dealing with aspects of social pedagogy analyzed by Hämäläinen, individually and collectively, such as the conceptual ambiguity of social pedagogy, the nature of social pedagogy as an academic discipline, social pedagogical guidance in social work and work with young people, ways of using the concept in Germany and Finland, as well as the field overview, including semantic and historical considerations. Other sources of information are also used, especially materials in which national traditions of social pedagogy and debates about their nature are introduced, compared, decoded and clarified. Methodologically, this work is based mainly on the analysis of historical concepts.